Ceramic-polymer-carbon composite coating on the truncated octahedron-shaped LNMO cathode for high capacity and extended cycling in high-voltage lithium-ion batteries - Pazhaniswamy, Sivaraj; Cha, Gihoon; Joshi, Sagar A; Parameswaran, Abhilash Karuthedath; Jose, Rajan; Pechmann, Sabrina; Christiansen, Silke; Agarwal, Seema (American Chemical Society (ACS Publications), 2024)
Long-term electrochemical cycle life of the LiNi0.5Mn1.5O4 (LNMO) cathode with liquid electrolytes (LEs) and the inadequate knowledge of the cell failure mechanism are the eloquent Achilles’ heel to practical applications despite their large promise to lower the cost of lithium-ion batteries (LIBs). Herein, a strategy for engineering the cathode–LE interface is presented to enhance the cycle life of LIBs. The direct contact between cathode-active particles and LE is controlled by encasing sol–gel-synthesized truncated octahedron-shaped LNMO particles by an ion–electron-conductive (ambipolar) hybrid ceramic–polymer electrolyte (IECHP) via a simple slot-die coating. The IECHP-coated LNMO cathode demonstrated negligible capacity fading in 250 cycles and a capacity retention of ∼90% after 1000 charge–discharge cycles, significantly exceeding that of the uncoated LNMO cathode (a capacity retention of ∼57% after 980 cycles) in 1 M LiPF6 in EC:DMC at 1 C rate. The difference in stability between the two types of cathodes after cycling is examined by focused ion beam scanning electron microscopy and time-of-flight secondary ion mass spectrometry. These studies revealed that the pristine LNMO produces an inactive layer on the cathode surface, reducing ionic transport between the cathode and the electrolyte and increasing the interface resistance. The IECHP coating successfully overcomes these limitations. Therefore, the present work underlines the adaptability of IECHP-coated LNMO as a high-voltage cathode material in a 1 M LiPF6 electrolyte for prolonged use. The proposed strategy is simple and affordable for commercial applications.